Medical Management of Crohn Disease - Scott, Frank I.; Osterman, Mark T. (Clinics in Colon and Rectal Surgery, 2013)
Crohn disease (CD) is one of the major subtypes of inflammatory bowel disease and can occur in any segment of the alimentary tract. There have been significant advances in the medical therapy of CD over the past several decades. For mild CD, the oral corticosteroid derivative budesonide has demonstrated superior efficacy compared with traditional therapies such as 5-aminosalicylic acid, and can be used concurrently with these agents. For the management of moderate to severe disease, the immunomodulators azathioprine, 6-mercaptopurine, and methotrexate, as well as the antitumor necrosis factor-alpha (TNF-α) agents infliximab, adalimumab, and certolizumab pegol, have become the mainstay of therapy, with growing interest in combining these agents for maximal effect. Immunomodulators and anti-TNF-α agents have also demonstrated benefit in fistulizing CD. There has been growing evidence suggesting that both of these agents, along with the antibiotics metronidazole and ornidazole, are also effective in preventing postoperative recurrence of CD.
Keywords: Crohn disease; antitumor necrosis factor-alpha; immunomodulators; 5-aminosalicylic acid; budesonide